Erôs and Self-Formation: A Platonic Approach - Dong, Didi (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Philosophy, 2026)
This dissertation examines the place and significance of erôs in Plato’s theory of self-formation, focusing on its role as the driving force in shaping and developing the self. It addresses a central question: What, for Plato, is the role or function of erôs in the formation of oneself or the self? The study analyses the dialogues in which Plato explicitly engages with the relationship between erôs and self-formation, primarily the Symposium, Phaedrus, Alcibiades, Lysis, and selected passages from the Republic. The dissertation advances two main theses, both intended in a descriptive sense. First, on Plato’s account, erôs is indispensable to self-formation: no genuine process through which the soul acquires a determinate character over time occurs without it. Second, erôs shapes the soul on two interconnected levels, by contributing to the establishment of its internal structure and order and by guiding the development of its external, interpersonal relations. In this dual role, erôs unites the soul’s inner dynamics with its social environment, showing that self-formation is both an inward transformation and an outward engagement with others.
None
APPROVED
Keywords: Plato; Self-Formation; Erôs